The Economic Effects of the Mega Sport Events on Tourism in the BRICS Countries Case - Iuliana Pop; Adrian Kanovici; Graţiela Ghic; Mădălina Andrei (Amfiteatru Economic Journal, 2016)
At the beginning of the 21st century, events tourism witnessed an impressive development in a series of countries due to the increase of the spare time and of the people's income, to the cheaper and more diversified world transport, especially the air transport and due to the emergence of new destinations. Emergent countries, such as China and Russia, recorded not only an increase in the number of tourists but also in the revenues from tourism activities. One of the reasons is the opening of these countries frontiers in order to reaffirm their power on international level (Golubchikov, 2016). Besides the relaxation, business and religious tourism, the sport tourism becomes more and more important. It also comprises the tourism for mega sport events, such as the Summer and Winter Olympics or the World Championships in different sports. For the organising countries, there is a real challenge to ensure the investments for the infrastructure, although it supports their economic development, being used after the sport events conclusion. Considering the available data from the World Bank and the World Tourism Organization (UNWTO), the authors make a quantitative investigation regarding the impact of the mega sport events on the tourism phenomenon in the BRICS countries. The article also researches a small and specific group of countries (BRICS), considering a niche tourism phenomenon. The article aims to emphasize the role of the mega sport events in the BRICS countries, directly connected with their capacity to economically support the organization of these events and also with the desire to internationally promote their national values.
Keywords: L83; O18; O57; 330; events tourism; mega sport events; emerging countries; BRICS countries